THE INFLUENCE OF INCOME AND LIFESTYLE ON CONSUMPTIVE BEHAVIOR: THE ROLE OF FINANCIAL LITERACY - Khoiriawati, Novi; Maulidiyah, Fatma Nur (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study is driven by the fact that people's consuming habits are changing due to the availability of increasingly advanced digital technologies, particularly in terms of shopping becoming more consumptive. All groups, even teens from generation Z, are susceptible to this consumptive habit. With financial literacy serving as a moderating variable, the aim of this study was to examine how generation Z's consumption patterns in Tulungagung Regency were impacted by lifestyle and income level. This study employs a quantitative methodology and an associative research design. Up to 100 respondents from generation Z in Tulungagung Regency completed questionnaires, which served as the major data source. The Slovin formula and proportionate stratified random sampling are the sampling methods employed. Using the SEM-PLS approach and the SmartPLS 4.0 program, questionnaire data were examined. 1) Income level has a favorable and considerable impact on consumption behavior, according to the study's findings. 2) Lifestyle significantly and favorably influences consumer behavior.3) The influence that income level has on consumer behavior can be mitigated (increased) by financial literacy. 4) Financial literacy can mitigate the impact of lifestyle choices on consumer behavior. 5) Lifestyle and income level have an impact on consumer behavior, whereas financial literacy acts as a moderating factor.